A numerical algorithm for optimal location of an air-pollution object - Duc, Nguyen The; Tran, Tran Van (Vietnam Journal of Mechanics, 1993)
On the base of the method suggested by G. I. Marchuc for the problem of optimal location of an air-pollution object1 such as newly built plant1 in a region in which one or several habitations arrange, in this paper a numerical algorithm is proposed. The Hybrid scheme applied for the three-dimensional transport equation permits to integrate it with large enough time step that is very important factor when the program is running on PC. As an example, a calculation for an arbitrary wind field is conducted.